Copper recovery from waste printed circuit boards by the flotation-leaching process optimized using response surface methodology. (2nd December 2021) - Wang, Chongqing; Sun, Ruirui; Xing, Baolin
ABSTRACT: Recycling of waste printed circuit boards (PCBs) receives increasing attention due to abundant metallic resources and significant environmental threats. This work proposes a process for copper recovery from PCBs by froth flotation and oxidation leaching. Copper grade is improved from 38.70% to 68.34% with the recovery of 88.76% by froth flotation, and froth flotation is significantly influenced by copper liberation and particles dispersion of PCB powders. Process variables of oxidation leaching are examined by response surface methodology (RSM). A reliable mathematical model is obtained to predict the response as a function of independent variables and their interactions. Oxidation leaching is remarkably influenced by experimental variables, and the interactions between sulfuric acid and hydrogen peroxide are significant. Optimum conditions are achieved as sulfuric acid 1.0 mol/L, hydrogen peroxide 17%, temperature 50°C, and time 234 minutes, and the maximum leaching ratio of Cu is up to 99.94%, indicating that oxidation leaching is an effective method for Cu recovery from PCBs. Implications : Recycling of waste printed circuit boards (PCBs) receives increasing attention due to abundant metallic resources and significant environmental threats. This work proposes a novel process for copper recovery from PCBs by froth flotation and oxidation leaching. Froth flotation is efficient to enrich copper in metal fractions. Process variables of oxidation leaching are examined by response surface methodology (RSM). A reliable mathematical model is obtained to predict the response as a function of independent variables and their interactions. The froth flotation-oxidation leaching process is practicable and effective for copper recovery from waste printed circuit boards. This study significantly contributes to recycling metal resources from waste PCBs. We believe that this work will attract a broad readership and lead others to follow our approach.